2011
DOI: 10.1007/s10211-011-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of maternal odors on foraging behavior during postnatal development in a solitary subterranean rodent Ctenomys talarum

Abstract: We investigated the role of maternal odors emanating from excretory deposits and/or glandular secretions during the postnatal development of foraging and related behaviors in young Los Talas' tuco-tucos (Ctenomys talarum), a solitary rodent, under seminatural conditions. During cafeteria tests, we offered them two of the grasses most preferred by adults of this species (bromegrass, Bromus unioloides and panicgrass, Panicum racemosum). We scent marked one dietary option in a treatment group, and the other optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Animals need to adaptively rely on social and asocial learning based on a trade‐off between the cost of collecting information and its reliability (Kendal et al, 2005). Echeverría and Vassallo (2012) found that although diet selection during weaning might be influenced by the mother, maternal influence was not essential for diet selection during dispersal in solitary rodents ( Ctenomys talarum ). Additionally, Galef and Whiskin (2001) provided experimental evidence that socially enhanced food preferences weaken after animals have experienced alternative foods, especially high‐quality alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Animals need to adaptively rely on social and asocial learning based on a trade‐off between the cost of collecting information and its reliability (Kendal et al, 2005). Echeverría and Vassallo (2012) found that although diet selection during weaning might be influenced by the mother, maternal influence was not essential for diet selection during dispersal in solitary rodents ( Ctenomys talarum ). Additionally, Galef and Whiskin (2001) provided experimental evidence that socially enhanced food preferences weaken after animals have experienced alternative foods, especially high‐quality alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…). In the case of Ctenomys , Echeverría & Vassallo () observed that, when foraging on the two preferred grasses, C . talarum (Los Talas’ tuco‐tuco) consumed both grasses through two different foraging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are cases such as rats (Rattus) which show the ability to perform a more precise manipulation of the food, even with a single hand (see references in Whishaw et al 1998). In the case of Ctenomys, Echeverr ıa & Vassallo (2012) observed that, when foraging on the two preferred grasses, C. talarum (Los Talas' tucotuco) consumed both grasses through two different foraging techniques. When foraging on panicgrass (Panicum racemosum) individuals handled the culm using both hands at once and rotated it for peeling the cataphylls using their incisors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have shown that the digging behaviour in different species of the genus Ctenomys is already present shortly after birth (Echeverría ; Echeverría and Vassallo ). Yet, in those taxa, this particular conduct involves both force production and the corresponding force reception.…”
Section: Introductionmentioning
confidence: 99%